At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Sure, let's solve the expression [tex]\((m+n+p)^2 - (m-n+p)^2\)[/tex] step-by-step.
### Step 1: Understanding the Expression
We need to evaluate the difference of the squares of two expressions: [tex]\(a = (m+n+p)\)[/tex] and [tex]\(b = (m-n+p)\)[/tex].
### Step 2: Using the Difference of Squares Formula
Recall that the difference of squares formula is:
[tex]\[ a^2 - b^2 = (a - b)(a + b) \][/tex]
Here, our [tex]\(a\)[/tex] is [tex]\((m+n+p)\)[/tex] and our [tex]\(b\)[/tex] is [tex]\((m-n+p)\)[/tex].
### Step 3: Calculate [tex]\(a - b\)[/tex]
Let's substitute [tex]\(a\)[/tex] and [tex]\(b\)[/tex] into [tex]\(a - b\)[/tex]:
[tex]\[ a - b = (m+n+p) - (m-n+p) \][/tex]
Simplifying this:
[tex]\[ a - b = m + n + p - m + n - p \][/tex]
The [tex]\(m\)[/tex] and [tex]\(-m\)[/tex] cancel each other out, and the [tex]\(p\)[/tex] and [tex]\(-p\)[/tex] cancel each other out:
[tex]\[ a - b = 2n \][/tex]
### Step 4: Calculate [tex]\(a + b\)[/tex]
Now let’s substitute [tex]\(a\)[/tex] and [tex]\(b\)[/tex] into [tex]\(a + b\)[/tex]:
[tex]\[ a + b = (m+n+p) + (m-n+p) \][/tex]
Simplifying this:
[tex]\[ a + b = m + n + p + m - n + p \][/tex]
The [tex]\(+n\)[/tex] and the [tex]\(-n\)[/tex] cancel each other out:
[tex]\[ a + b = 2m + 2p \][/tex]
### Step 5: Multiply [tex]\(a - b\)[/tex] and [tex]\(a + b\)[/tex]
From the previous steps, we have:
[tex]\[ a - b = 2n \][/tex]
[tex]\[ a + b = 2m + 2p \][/tex]
Now, multiply these two results:
[tex]\[ (a - b)(a + b) = (2n)(2m + 2p) \][/tex]
Distribute [tex]\(2n\)[/tex] across [tex]\(2m + 2p\)[/tex]:
[tex]\[ (2n)(2m) + (2n)(2p) = 4mn + 4np \][/tex]
### Step 6: Final Answer
Thus, [tex]\((m+n+p)^2 - (m-n+p)^2\)[/tex] evaluates to:
[tex]\[ 4mn + 4np \][/tex]
Considering the given specific values, [tex]\(m = 1\)[/tex], [tex]\(n = 2\)[/tex], and [tex]\(p = 3\)[/tex], the numerical result of the expression is:
[tex]\[ 32 \][/tex]
So, the solution is [tex]\(4mn + 4np = 32\)[/tex].
### Step 1: Understanding the Expression
We need to evaluate the difference of the squares of two expressions: [tex]\(a = (m+n+p)\)[/tex] and [tex]\(b = (m-n+p)\)[/tex].
### Step 2: Using the Difference of Squares Formula
Recall that the difference of squares formula is:
[tex]\[ a^2 - b^2 = (a - b)(a + b) \][/tex]
Here, our [tex]\(a\)[/tex] is [tex]\((m+n+p)\)[/tex] and our [tex]\(b\)[/tex] is [tex]\((m-n+p)\)[/tex].
### Step 3: Calculate [tex]\(a - b\)[/tex]
Let's substitute [tex]\(a\)[/tex] and [tex]\(b\)[/tex] into [tex]\(a - b\)[/tex]:
[tex]\[ a - b = (m+n+p) - (m-n+p) \][/tex]
Simplifying this:
[tex]\[ a - b = m + n + p - m + n - p \][/tex]
The [tex]\(m\)[/tex] and [tex]\(-m\)[/tex] cancel each other out, and the [tex]\(p\)[/tex] and [tex]\(-p\)[/tex] cancel each other out:
[tex]\[ a - b = 2n \][/tex]
### Step 4: Calculate [tex]\(a + b\)[/tex]
Now let’s substitute [tex]\(a\)[/tex] and [tex]\(b\)[/tex] into [tex]\(a + b\)[/tex]:
[tex]\[ a + b = (m+n+p) + (m-n+p) \][/tex]
Simplifying this:
[tex]\[ a + b = m + n + p + m - n + p \][/tex]
The [tex]\(+n\)[/tex] and the [tex]\(-n\)[/tex] cancel each other out:
[tex]\[ a + b = 2m + 2p \][/tex]
### Step 5: Multiply [tex]\(a - b\)[/tex] and [tex]\(a + b\)[/tex]
From the previous steps, we have:
[tex]\[ a - b = 2n \][/tex]
[tex]\[ a + b = 2m + 2p \][/tex]
Now, multiply these two results:
[tex]\[ (a - b)(a + b) = (2n)(2m + 2p) \][/tex]
Distribute [tex]\(2n\)[/tex] across [tex]\(2m + 2p\)[/tex]:
[tex]\[ (2n)(2m) + (2n)(2p) = 4mn + 4np \][/tex]
### Step 6: Final Answer
Thus, [tex]\((m+n+p)^2 - (m-n+p)^2\)[/tex] evaluates to:
[tex]\[ 4mn + 4np \][/tex]
Considering the given specific values, [tex]\(m = 1\)[/tex], [tex]\(n = 2\)[/tex], and [tex]\(p = 3\)[/tex], the numerical result of the expression is:
[tex]\[ 32 \][/tex]
So, the solution is [tex]\(4mn + 4np = 32\)[/tex].
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.